Revealing Privilege—Why Bother? - Danielle K. Hart (Washington University Journal of Law & Policy, 2013)
Fifteen years ago, Stephanie Wildman wrote a provocative and compelling book entitled Privilege Revealed: How Invisible Preference Undermines America, with contributions by Margalynne J. Armstrong, Adrienne D. Davis, and Trina Grillo. In a thorough but concise examination of different and seemingly unrelated topics including, among others, housing, the workplace, and language, Wildman made visible what was and, unfortunately, remains the hidden but normative baseline of whiteness, maleness, and heterosexuality against which all “others” are judged. More than that, the book revealed that institutionalized but invisible systems of privilege define and continue to uphold the status quo. In this short Essay, I delineate what I perceive to be Wildman’s challenge to progressives to reveal privilege in the work we do. But I also question whether taking up Wildman’s call to arms is even worth doing. After all, as Derrick Bell told us, inequality is here to stay. So, why bother challenging it? The short, honest answer is that we challenge inequality because we must. Professor Kie Hart therefore takes up Wildman’s challenge by revealing privilege in contract law in the form of class privilege and bargaining power.
Keywords: Privilege Revealed; privilege; class privilege; contract law; bargaining power and privilege; property and privilege